The Effect of Service Quality and Mobile Banking Applications on Customer Loyalty with Satisfaction as a Mediating Variable in Suryopranoto Branch Bca Customers - Feliciana, Feliciana; Saparso, Saparso; Lizardo, Jimmy (Maneggio, 2024)
This study explores the impact of service quality and mobile banking applications on customer loyalty, with customer satisfaction acting as a mediating factor (focusing on patrons of BCA Suryopranoto). The quantitative methodology examines hypotheses through a dataset comprising 280 customer responses. These responses were collected via direct surveys distributed to the customers. The Partial Least Structural Equation Modeling (PLS-SEM) technique was utilized for the analysis, specifically through SmartPLS 3.2.8 software. The data processing and analysis outcomes reveal that service quality and mobile banking applications significantly affect customer loyalty, which is crucial in mediating customer satisfaction. Research findings indicate that directly addressing service quality, mobile banking applications, and customer loyalty is pivotal in achieving customer satisfaction.